2003
DOI: 10.1097/01.lab.0000101732.89463.29
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Mutations of the BRAF Gene and Constitutive Activation of Extracellular-Regulated Kinase in Malignant Melanomas of the Uvea

Abstract: SUMMARY:The v-raf murine sarcoma viral homolog B1 (BRAF) gene, one of the human isoforms of RAF, is activated by Ras, leading to cooperative effects in cells responsive to growth factor signals. Recently, somatic missense mutations of the BRAF gene have been detected in more than 66% of malignant melanomas of the skin. We analyzed 42 malignant melanomas of the uvea, 3 corresponding liver metastases, and 10 cutaneous melanomas for possible BRAF mutations: after microdissection, mutation analysis of BRAF and KRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 23 publications
(29 reference statements)
3
76
0
1
Order By: Relevance
“…Similarly, our observation of a complete lack of BRAF mutations in primary uveal tumours mirrors the findings of several recent reports (Cohen et al, 2003;Cruz et al, 2003;Edmunds et al, 2003;Rimoldi et al, 2003;Weber et al, 2003;Kilic et al, 2004). Table 3 contains a summary of published reports on RAS and BRAF mutations, as well as studies on other members of the MAPK pathway, in uveal melanomas.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, our observation of a complete lack of BRAF mutations in primary uveal tumours mirrors the findings of several recent reports (Cohen et al, 2003;Cruz et al, 2003;Edmunds et al, 2003;Rimoldi et al, 2003;Weber et al, 2003;Kilic et al, 2004). Table 3 contains a summary of published reports on RAS and BRAF mutations, as well as studies on other members of the MAPK pathway, in uveal melanomas.…”
Section: Discussionsupporting
confidence: 77%
“…The signal transducer MEK1/2 phosphorylates extracellular signal-regulated kinase (ERK1/2, p44/42), leading to the activation of these kinases, which in turn activate a variety of transcription factors, including ELK1, again through phosphorylation. It has emerged that BRAF (v-raf murine sarcoma viral oncogene homologue B1) is very frequently activated by mutation in cutaneous melanomas (Brose et al, 2002;Davies et al, 2002;Alsina et al, 2003;Dong et al, 2003;Gorden et al, 2003;Kumar et al, 2003a, b;Maldonado et al, 2003;Omholt et al, 2003;Pollock et al, 2003;Rimoldi et al, 2003;Satyamoorthy et al, 2003;Weber et al, 2003;Cohen et al, 2004;Reifenberger et al, 2004;Shinozaki et al, 2004;Tsao et al, 2004). The frequency of BRAF mutations varies from 8 to 83% depending on the anatomic site of the lesion and its histogenic subtype.…”
mentioning
confidence: 99%
“…However, there have been several studies, in uveal melanoma including primary and metastatic choroidal and ciliary body melanomas and the BRAF mutation has only been identified in one case (Malaponte et al, 2006). Despite this apparent lack of the characteristic BRAF mutation, inappropriate downstream MAPK component activation has been reported by Weber et al (2003) who failed to identify the BRAF mutation in 42 primary uveal melanoma but showed immunohistochemical staining for ERK in 86% of these cases. Similarly, Zuidervaart et al (2005) found constitutive activation of the MAPK pathway in 11 uveal melanoma cell lines and 19 primary tumours by performing western blot or immunohistochemistry for the various pathway components.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of other studies have used some form of direct sequencing to identify this mutation (Cruz et al, 2003;Edmunds et al, 2003;Weber et al, 2003). Sequencing would not be able to detect mutant alleles present at low frequency because of somatic mosaicism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation